1996
DOI: 10.1148/radiology.199.3.8638013
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial wall thickness: appropriate window settings for thin-section CT and radiologic-anatomic correlation.

Abstract: Bronchial wall thickness on thin-section CT scans should be evaluated with window centers between -250 and -700 HU and with window widths greater than 1,000 HU. Other than window settings, notably window widths less than 1,000 HU, can lead to substantial artificial thickening of bronchial walls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(43 citation statements)
references
References 0 publications
0
42
0
1
Order By: Relevance
“…However, this process is not only very labor intensive and subject to large inter-and intraobserver error (10)(11)(12), but is also extremely dependent on the display parameters of the CT image. Investigators showed that the airway could only be accurately measured using a CT window level of 2450 HU and a window width of 1,000 to 1,400 HU (10)(11)(12)(13). While these images allow one to measure airways, they are not suitable for clinical uses, and since a printed version of the CT scan was the most common version of the CT images at that time, these images were rarely produced.…”
Section: Airway Analysismentioning
confidence: 99%
“…However, this process is not only very labor intensive and subject to large inter-and intraobserver error (10)(11)(12), but is also extremely dependent on the display parameters of the CT image. Investigators showed that the airway could only be accurately measured using a CT window level of 2450 HU and a window width of 1,000 to 1,400 HU (10)(11)(12)(13). While these images allow one to measure airways, they are not suitable for clinical uses, and since a printed version of the CT scan was the most common version of the CT images at that time, these images were rarely produced.…”
Section: Airway Analysismentioning
confidence: 99%
“…In the initial studies in which airway dimensions were measured using CT, the investigators relied on manual tracing of the airway images [11][12][13][14][15]. These techniques are extremely time consuming and prone to error.…”
Section: Quantitative Assessment Of Larger Airwaysmentioning
confidence: 99%
“…Several groups have investigated optimal window settings for quantitative airway measurements [19,[24][25][26][27]. While most studies in phantoms have shown that window level and not width determines the accuracy with which the airway lumen [19,27] and wall area [25] are measured, BANKIER et al [24], using inflation-fixed cadaveric lungs, found window width rather than level affected this accuracy. This suggests that phantom studies may not reflect in vivo conditions in which partial volume averaging plays an important role.…”
Section: Limits Of Ct Resolutionmentioning
confidence: 99%
“…As CT slices are two-dimensional images representing three-dimensional data it follows that, when airways are imaged at angles other than 90u, more wall area, derived from the z axis, is incorporated into the x and y dimensions leading to an apparent increase in wall thickness and decrease in lumen area ( fig. 2) [24]. Thinner slices and more orthogonal airway scanning therefore lessen the degree of partial voluming averaging [9,27].…”
Section: Measuring Airway Dimensions From Ct Datamentioning
confidence: 99%